2018
DOI: 10.1038/s41598-018-21601-9
|View full text |Cite|
|
Sign up to set email alerts
|

Understanding the functional role of genistein in the bone differentiation in mouse osteoblastic cell line MC3T3-E1 by RNA-seq analysis

Abstract: Genistein, a phyto-estrogen, can potentially replace endogenous estrogens in postmenopausal women, but the underlying molecular mechanisms remain incompletely understood. To obtain insight into the effect of genistein on bone differentiation, RNA sequencing (RNA-seq) analysis was used to detect differentially expressed genes (DEGs) in genistein-treated vs. untreated MC3T3-E1 mouse osteoblastic cells. Osteoblastic cell differentiation was monitored by measuring osteoblast differentiation factors (ALP production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…55 In addition, genistein and daidzein also induce osteoblastic differentiation and angiogenesis on bone formation. [56][57][58] In the present study, Jix inhibited Pg infection and decreased alveolar bone resorption. Osteoblasts appear on tension side to promote new bone formation.…”
Section: Effect Of Jix On Otmsupporting
confidence: 58%
“…55 In addition, genistein and daidzein also induce osteoblastic differentiation and angiogenesis on bone formation. [56][57][58] In the present study, Jix inhibited Pg infection and decreased alveolar bone resorption. Osteoblasts appear on tension side to promote new bone formation.…”
Section: Effect Of Jix On Otmsupporting
confidence: 58%
“…In MC3T3 pre-osteoblastic cells, treatment with genistein altered the expression levels of genes associated with cell proliferation, cell migration, cell differentiation, and inflammatory responses. Successive knockdown analyses showed that two upregulated genes (Ereg and Efcab2) and three downregulated genes (Hrc, Gli1, and Iftm5) play crucial roles in the differentiation of osteoblasts via increasing the expressions of osteoblast-associated markers such as RUNX2, ALP and BMP-2 ( 146 ). Administration of genistein to human bone marrow stromal cells suppressed its differentiation into adipocytes by inhibiting the mRNA levels of PPARg and CCAAT/enhancer binding proteins (C/EBPs), while it enhanced osteoblastogenesis, thus preventing bone loss associated with excessive adipogenesis ( 147 ).…”
Section: Classification Of Flavonoidsmentioning
confidence: 99%
“…In vivo, genistein attenuated cartilage degradation in two different OA animal models [ 58 , 59 ]. Furthermore, a positive effect on bone was obtained through enhanced osteoblastic differentiation and maturation via the activation of ER (estrogen receptor), p38 MAPK–Runx2, and NO/cGMP pathways [ 60 , 61 , 62 ]. It also inhibited osteoclast formation and bone resorption by inducing the osteoclastogenic inhibitor osteoprotegerin (OPG) and by blocking NF-κB signaling [ 60 , 63 ].…”
Section: Natural-compound-based Treatments For Oa Therapymentioning
confidence: 99%